2020
DOI: 10.21203/rs.3.rs-76099/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Reciprocal Effects of Physical Activity and Happiness in Adolescents

Abstract: BackgroundPositive associations exist between physical activity and happiness in adolescents. However, previous studies have mostly used self-reported measures and cross-sectional designs. There is a need for more insight into the directionality and duration of this association. The current study was the first to investigate whether an increase in physical activity leads to happiness and whether adolescents become more physically active when they are happier. These two effects were studied between (on a day-to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, experimental studies in adolescents mostly observe benefits on mental health after applying a PA intervention (Hale et al, 2021). Moreover, according to a recent study with a day-by-day design (micro-longitudinal), it seems that the relationship could be even bidirectional, but only in the very short term (within the same day) (Van Woudenberg et al, 2020). Nevertheless, in the study authors considered only steps per day and happiness as a PA and psychological measures respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experimental studies in adolescents mostly observe benefits on mental health after applying a PA intervention (Hale et al, 2021). Moreover, according to a recent study with a day-by-day design (micro-longitudinal), it seems that the relationship could be even bidirectional, but only in the very short term (within the same day) (Van Woudenberg et al, 2020). Nevertheless, in the study authors considered only steps per day and happiness as a PA and psychological measures respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal studies showed a long-term relationship between PA and psychological constructs, but the results are inconsistent (Wu et al, 2018 , 2021 ; Doré et al, 2019 , 2020 ; Kleppang et al, 2019 ; Loewen et al, 2019 ; Gómez-Baya et al, 2020 ; Hamer et al, 2020 ; Isaksson et al, 2020 ; Kandola et al, 2020 ; van Woudenberg et al, 2020 ; Bowe et al, 2021 ). To illustrate some results, Nigg et al concluded that PA may not be a preventive component for mental health problems, but mental health problems can be a risk factor for lower activity at preadolescent ages (Nigg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individual studies have small and non-representative samples (Ahn et al, 2018 ; Bowe et al, 2021 ; Mercurio et al, 2021 ), low quality, no long-term follow-ups, and inadequate consideration of real-world implementation factors for intervention studies (Parker et al, 2019 ). In many longitudinal studies, there is a lack of repeated measurements of either PA or mental health outcomes (Ahn et al, 2018 ; Peralta et al, 2018 ; Bell et al, 2019 ; Doré et al, 2019 , 2020 ; Kleppang et al, 2019 ; Hamer et al, 2020 ; Pagani et al, 2020 ; van Woudenberg et al, 2020 ; Bowe et al, 2021 ; Wu et al, 2021 ). Also, a focus on specific mental health outcomes (Rodriguez-Ayllon et al, 2019 ) and less frequent use of multidimensional measurements (Bell et al, 2019 ) are further limitations that should be mentioned.…”
Section: Introductionmentioning
confidence: 99%